2021
DOI: 10.3390/ijms22126501
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Liquid Biopsy for Cancer Detection Is Improved by Using Cationic Dendronized Hyperbranched Polymer

Abstract: (1) Background: Biophysical techniques applied to serum samples characterization could promote the development of new diagnostic tools. Fluorescence spectroscopy has been previously applied to biological samples from cancer patients and differences from healthy individuals were observed. Dendronized hyperbranched polymers (DHP) based on bis(hydroxymethyl)propionic acid (bis-MPA) were developed in our group and their potential biomedical applications explored. (2) Methods: A total of 94 serum samples from diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…(4) The materials utilized must exhibit superior biocompatibility. In fact, with the increasing research on the application of material science in medicine, recent studies have unveiled the distinctive potential of certain nanomaterials and polymers in enhancing liquid biopsy and imaging methodologies [ [11] , [12] , [13] , [14] ]. Additionally, the utilization of luminescent materials like indocyanine green (ICG) has spurred advancements in bioimaging techniques for the early detection of renal cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…(4) The materials utilized must exhibit superior biocompatibility. In fact, with the increasing research on the application of material science in medicine, recent studies have unveiled the distinctive potential of certain nanomaterials and polymers in enhancing liquid biopsy and imaging methodologies [ [11] , [12] , [13] , [14] ]. Additionally, the utilization of luminescent materials like indocyanine green (ICG) has spurred advancements in bioimaging techniques for the early detection of renal cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…When excited at suitable wavelengths, some biomolecules emit radiation over a wide spectral range in the ultraviolet–visible region. Changes in serum composition will be reflected in changes occurring in biochemical, physicochemical, and histological properties, and in particular, changes in the fluorescence emission spectrum [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…To develop a fluorescence liquid biopsy (FLB) analysis technique, Morcuende-Ventura et al prepared fluorescent dendronized hyperbranched polymers (DHP) created from bis(hydroxymethyl)propionic acid [ 49 ]. The output of this study indicated that the inclusion of DHP-bMPA improved the classification performance of FLB in diagnosing pancreatic and ovarian cancers, with a performance reaching 85% (specificity and selectivity) for both pathologies.…”
Section: Application Of Polymers In Liquid Biopsy-based Diagnosismentioning
confidence: 99%